Communally breeding female Barn Owls Tyto alba are not related and do not invest similarly in the communal family. Issue 4 (2nd October 2019) - Séchaud, Robin; Machado, Ana Paula; Schalcher, Kim; Simon, Céline; Roulin, Alexandre
ABSTRACT: We report detailed information about relatedness and parental investment in a communal nest in the Barn Owl Tyto alba . Two unrelated females laid their eggs in a single nest cup and successfully raised 4 nestlings out of 11 laid eggs. Apparently, the yearling female did not incubate the eggs and only occasionally hunted for the brood, in contrast to the older female which invested more effort in parental care.